Effects of diet formulation on pellet mill performance and pellet quality on grow-finish pig growth performance - Badger, Patrick Alan (Kansas State University, 2023)
A total of 4 experiments were conducted to determine the effects of diet formulation on pellet mill production parameters, subsequent pellet qualities and the effects of pellet die thickness and pellet quality on grow-finish pig growth performance. Pellet mill production rates can directly affect pelleting costs due to diet costs being able to be divided by a larger denominator of feed produced. However, it has been generally accepted that increasing pellet mill production rates has a negative effect on pellet quality. Therefore, the first two experiments were conducted to evaluate the impact of pellet mill electrical consumption, pellet mill production rates, and subsequent pellet qualities. Exp. 1 was conducted at a commercial feed mill and set as a 2 × 2 × 2 factorial with main effects of diet formulation (0 or 30% DDGS inclusion), Azomite® (AZO; Azomite Feed Grit, Nephi, UT) inclusion (0 or 0.25%), and pellet mills (1 or 2; both mills were 500-horsepower, Andritz, Model 32-700, Esbjerg, Denmark). There were a total of 4 replications per treatment per pellet mill. Pellet mills were equipped with either 4.4 × 39.0 mm (L:D 8.9) or 4.4 × 35.8 mm (L:D 8.2) and production rates were held constant at 31.75 MT per hour. Conditioning temperature was held constant at 82℃. Treatment replications consisted of 43.54 MT with a 43.54 MT “flush” pelleted after any treatment containing AZO to recoat the pellet mill die with feed particles. Exp. 1 resulted in a DDGS × PM interaction (P = 0.040) with the inclusion of DDGS increased pellet mill kWh/MT in PM 2 while electrical consumption was decreased by DDGS inclusion in PM 1. For kWh/MT standard deviation (STD), an AZO × DDGS (P = 0.026) interaction was observed in that there were no differences in kWh/MT STD for 0% DDGS whereas AZO inclusion reduced kWh/MT STD for diets containing 30% DDGS. PDI was reduced (P < 0.05) by AZO inclusion in the diet. However, the inclusion of 30% DDGS improved (P < 0.05) PDI compared to treatments without DDGS. Exp. 2 was conducted at the O.H. Kruse Feed Technology and Innovation Center at Kansas State University (Manhattan, KS). Exp. 2 was designed as a 2 × 2 factorial in a 4 × 4 Latin Square design with main effects of diet formulation (0 or 30% DDGS) and AZO inclusion (0 or 0.25%) to evaluate the impact of pellet mill production rates (California Pellet Mill, 3016-4) and subsequent pellet quality. Treatments were replicated 4 times over 4 separate days. Treatment replications consisted of 2.72 MT with pellet mill motor load held constant at 70% by adjusting the pellet mill feeder VFD. For Exp. 2, the inclusion of AZO to the diet increased (P < 0.05) pellet mill production rates. Whereas the inclusion of 30% DDGS reduced (P < 0.05) pellet mill production rate. There was a tendency for an AZO × DDGS interaction (P = 0.0828) with no differences in PDI’s for treatments containing DDGS but the PDI’s were reduced with the inclusion of AZO. In conclusion the addition of AZO reduces pellet mill electrical consumption and improves pellet mill production rate while reducing PDI’s when conditioning temperatures remain constant. Exp. 3 was conducted to determine the effects of pellet quality on pig growth performances over three distinct weight ranges. A total of 350 pigs (line 600 × 241; DNA) were fed over three weights ranges. Pigs were weighed before each weight range with pens randomized to treatment for each weight range. There were 35 total pens with 10 pigs per pen and 7 replications per treatment. Pigs were fed experimental treatments for 20, 21, and 20 days for weight range 1, 2, and 3, respectively. Treatments consisted of a mash control and pellets with fines included at 9-16, 41-47, 60-68, and 84-91%. A 10-day washout period was used between each weight range where a common diet was fed to alleviate residual carryover of pelleted treatments. For weight range 1, 44-68 kg, pigs fed pellets with 13% fines had increased (P < 0.05) G:F compared to pigs fed the mash. Pigs fed pellets had increased (linear, P = 0.006) ADFI as pellet fines increased at the feeder. Whereas pig G:F decreased (linear, P = 0.002) as percent fines at the feeder increased. For weight range 2, 81-106 kg, pigs fed pellets with 16% fines at the feeder had improved (P < 0.05) G:F compared to pigs fed mash. Pigs fed 86% fines at the feeder had a tendency (P < 0.10) for increased ADFI compared to pigs fed mash, whereas pig G:F tended (P < 0.10) to decrease compared to pigs fed mash. Pig ADFI increased (linear, P = 0.016) as pellet fines percentage increased at the feeder. G:F improved (linear, P = < 0.001) as percent fines at the feeder decreased. For weight range 3, 118-144 kg, pigs fed pellets with fines inclusion up to 42% had increased (P < 0.05) G:F compared to pigs fed mash. Pigs fed pellets with 65% fines tended (P < 0.10) to have increased G:F when compared to pigs fed mash. Pigs fed pellets with 84% fines tended (P < 0.10) to have increased final BW and ADFI compared to pigs fed mash feed. Pig G:F increased (linear, P = 0.005) as the percentage of pellet fines decreased at the feeder. In conclusion, pigs fed pellets with minimal fines had the greatest improvement in growth responses with ADFI and G:F being negatively affected in a linear fashion as pellet fines increases at the feeder. Experiment 4 was conducted to evaluate the effects of pellet die thickness and screening pellet fines prior to delivery of feed on pig growth performances. A total of 314 pigs (line 600 × 241; DNA, initially 52 kg) were fed treatments consisting of either mash, L:D 8.75 pellets, L:D 5.5 pellets fed as-is, L:D 5.5 screened pellets, and pellet fines for 76 days. Pigs were placed in 35 pens with 9 pigs per pen and 7 replications per treatment. Pelleted treatments resulted in 27.82, 42.10, and 36.90% fines at the feeder for L:D 8.75, L:D 5.5 as-is, and L:D 5.5 screened pellets, respectively. Pigs fed L:D 8.75 pellets had increased (P < 0.05) day 76 BW compared to pigs fed mash or L:D 5.5 pellets fed as-is. Pigs fed L:D 8.75 pellets had increased (P < 0.05) ADG compared to pigs fed mash, L:D 5.5 pellets fed as-is, or pellet fines. Pigs fed L:D 8.75 pellets had improved (P < 0.05) G:F compared to pigs fed mash or L:D 5.5 pellets fed as-is. Pigs fed L:D 8.75 tended (P < 0.10) to have increased HCW compared to pigs fed L:D 5.5 pellets as-is. In conclusion, increasing pellet die thickness improved pig growth performance, which is largely attributed to reduction to pellet fines present at the feeder.
Keywords: Pellet mill; Distillers dried grains with solubles; Electrical consumption; Pellet quality; Pellet fines